THE PERCEPTION OF SCIENCE TEACHERS ON SOCIO-SCIENTIFIC ISSUES AND TEACHING THEM - Öztürk, Nurhan; Erabdan, Hilal (International Online Journal of Education and Teaching, 2019)
The present research aimed to analyse the perception of science teachers on socio-scientific issues and teaching them. The study group of the research consists of 22 science teachers (14 females, 8 males) working in 7 secondary schools in Sinop, who were determined according to the convenience sampling method. The case study as one of the qualitative research designs was adopted. The data source of the research consists of a questionnaire on teaching socio-scientific issues. The data of the research were obtained through focus group discussions and observation notes. The data obtained from the research were analysed according to the content analysis technique. As a result of the research, it was found out that most of the science teachers had not heard of the concept of SSI (socio-scientific issues) before. It was seen that teachers who did not have knowledge about SSI generally defined it as scientific issues that concern society and had difficulty in giving examples. It was determined that most of the teachers did not know to which learning area in the science curriculum SSI belonged. Teachers who stated that they mostly use the direct instruction, case study and discussion methods in the teaching of SSI in science course emphasised that the SSI teaching process makes positive contributions to the development of student skills like critical thinking, decision making and communication. Key words: Socio-scientific issues, teaching socio-scientific subjects, science teacher, science curriculum